Evaluation of the incisive papilla as a guide to maxillary canine position in the moradabad population: An anthropometric analysis - Siddhi Tripathi; Sujata Pandey; Swatantra Agarwal; Pratyushman Hazarika (Wolters Kluwer Medknow Publications, 2019)
Introduction: Incisive papilla has been used as a fixed anatomical landmark to guide teeth arrangement. However, controversy exists in literature whether to use anterior, middle, or posterior border of the incisive papilla for the determination of position of maxillary canines. Hence, a study was planned to ascertain the location of the incisive papilla to the intercanine line in a sample of population reporting to a teaching institute in Moradabad. Materials and Methods: A total of 200 participants aged 20-40 years were selected for the study. Impressions of the maxillary arches were made, and the casts were poured. The anterior point, midpoint, and posterior point of the incisive papilla and the tips of canines were marked on the cast. Photographs were taken and analyzed using Adobe Photoshop 7.0. The intercanine line was analyzed to assess whether it passed through the anterior, middle, or posterior border of the incisive papilla. Results: The Chi-square test revealed that there was a statistically significant difference (P < 0.05) of intercanine line in relation to different borders of the incisive papilla. The intercanine line passed through the anterior border of the incisive papilla in 8% of the participants, the middle border in 33.5% of the participants, between the middle and posterior border in 17.5% of the participants, and the posterior border in 41% of the participants. Conclusions: It was concluded that the intercanine line passed through the posterior border of the incisive papilla in maximum cases followed by the middle third, middle-posterior, and least through the anterior border of the incisive papilla. Hence, the posterior border of the incisive papilla is a reliable indicator for the placement of maxillary canines.